EDUKASI PENCEGAHAN KANKER SERVIKS SEDARI DINI DENGAN VAKSINASI HPV BAGI SISWA SDN 44 PADANG - Shelvy Haria Roza; Suci Maisyaroh Nasution; Nindi Oktaviani; Afifah Khairunnisa Puteri Effendi; Zerly Affi Walti (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
The main risk factor for cervical cancer is Human Pappiloma Virus (HPV) infection. One of the primary prevention efforts that can be done is HPV vaccination, which has been proven effective in reducing the risk of women being exposed to HPV infection. In Indonesia, cervical cancer is the second most common cancer in women after breast cancer. West Sumatra Province has the highest prevalence of cervical cancer, which is ranked second in Indonesia at 2.47 per 1000 population. The government has made it mandatory to provide free HPV vaccination for school children to prevent cervical cancer in the future, but the vaccination coverage is still low due to various anti-vaccine stigmas, many refusals from parents for vaccines. The existence of this rejection and stigma is a lack of information to the public about the effectiveness of the HPV vaccine. Therefore, it is necessary to socialize and educate the target of HPV vaccination to elementary school children in grades 5 and 6. The purpose of this activity is to increase the knowledge of school students about cervical cancer and its prevention with health education. The activity was held at SDN 44 Kalumbuk, Padang. The method in service begins with situation analysis, preparation and planning of activities, implementation, and evaluation. The results of the activity were an increase in the average knowledge of participants from 62.5 to 76.3 with an average increase of 13.8 points. This educational activity can increase participants' knowledge about cancer.